KINERJA PUSTAKAWAN DALAM PEMBERIAN PELAYANAN PUBLIK PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SUMATERA SELATAN - Wahyuli, Yofitri Heny (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This study aims to analyze and explain the performance of librarians in providing public services at the South Sumatra Province Library and Archives Service and to explain the inhibiting factors of librarian performance in providing public services. The low competence of librarian human resources and the lack of number of librarians in the Soeman HS public library managed by the South Sumatra Province Library and Archives Service, means that the number of services available and the amount of workload is not balanced. The research method used is a qualitative approach. Data collection techniques in the form of interviews, observation, and documentation. while the research informants who were included by researchers were 12 (twelve) people. The results of this study explain that the performance of librarians in providing public services at the Riau Province Library and Archives Service is quite good according to their main duties and functions. However, in the context of Human Resources, qualified librarians are still needed through appointments made by the Regional Government or from librarianship training with the aim that services at the South Sumatra Province Library and Archives Service can improve. If seen from the performance indicators based on Sedarmayanti's theory, there are still inhibiting factors for librarian performance in providing public services at the South Sumatra Province Library and Archives Service, namely. Judging from the work quality indicators, there is still a lack of user guidance for novice users who need to get various information and facilities needed available in the library; Judging from the timeliness indicator, there is still a lack of discipline in returning books. Judging from the Initiative Indicators, there is still a lack of cooperation with schools in Palembang City. Judging from the Capability Indicator, there is still a lack of individual librarian competence. Judging from the communication indicators, there is still a lack of information guides in the Soeman HS library. Librarians need to improve performance in providing services in terms of quality and quantity of work by participating in training or technical guidance to increase competence.